(untitled) (Revista NUPEART, 2021)
Through this article, it was intended to discuss about gender theories and notions, starting from the perspective of the american thinker Judith Butler (1990a; 2019b), of how patriarchal structures are strongly reproduced in a social context, especially by individuals who are imprisoned by standards culturally imposed by compulsory heteronormativity. Considering these passing rituals (GENNEP, 2011) and life crisis rituals (TURNER, 2005), the artist-researcher, proponent of this communication, in partnership with the Research and Extension Group CRUOR Arte Contemporânea of ​​XXXX and men free themselves, it took to the streets a manifesto to contest those already solid structures. In this way, a tripod for interlocution between gender notions, behavior patterns and urban performance acts in corality is erected.